2020
DOI: 10.3390/app10248847
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Control and Protection Architecture for Islanded PV-Battery DC Microgrids: Design, Analysis and Experimental Verification

Abstract: Direct current (dc) microgrids have gained significant interest in research due to dc generation/storage technologies—such as photovoltaics (PV) and batteries—increasing performance and reducing in cost. However, proper protection and control systems are critical in order to make dc microgrids feasible. This paper aims to propose a novel integrated control and protection scheme by using the state-dependent Riccati equation (SDRE) method for PV-battery based islanded dc microgrids. The dc microgrid under study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Most of the earlier research in the control and stability analysis of DC MG considers single or two DC/DC converters in their analysis and ignores the rest of the DC MG. Moreover, the PV source is generally modelled by a constant voltage source [31]. On the contrary, in this paper, the PV source is modelled by a well-known and practical model [8,10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the earlier research in the control and stability analysis of DC MG considers single or two DC/DC converters in their analysis and ignores the rest of the DC MG. Moreover, the PV source is generally modelled by a constant voltage source [31]. On the contrary, in this paper, the PV source is modelled by a well-known and practical model [8,10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To alleviate this concern, governments have announced strict deadlines to replace ICEVs with electric vehicles (EVs). For instance, the European Union (EU) has introduced a plan to ban the sale of ICEVs by 2035 [4][5][6][7]. Tese policies have encouraged the automotive industry to invest in EVs, as it is reported that it will spend at least $ 300 billion over the next ten years to develop EVs [8].…”
Section: Introductionmentioning
confidence: 99%
“…The protection of an MG is a complex and challenging task, because of different factors such as the MG operation modes and its bidirectional power flow, varying fault current contribution, limited and low level of fault current in power electronics-based power converter DGUs, high impedance faults (HIF), variable configuration of MG due to plug and play characteristics of DGUs [11,12], and low-voltage ride through (LVRT) requirements during a fault to prevent from system collapse [13]. In addition, the capacity and location of DGUs are important to define the setting of directional over current relays (DOCR) [14], which may influence the setting of protection devices (PD), such as pickup current (Ip), and time multiplier setting (TMS).…”
Section: Introductionmentioning
confidence: 99%